OBSESSIVE-COMPULSIVE DISORDER: THE RELATIONSHIP BETWEEN DYSFUNCTIONAL BELIEFS, SPIRITUAL GUILT, AND MENTAL REPETITIONS - Carvalho, William Silva (Revista Sistemática, 2023)
Obsessive-Compulsive Disorder (OCD) is a multifaceted psychiatric condition characterized by intrusive, unwanted thoughts (obsessions) and repetitive behaviors or mental acts (compulsions) aimed at reducing distress. This article investigates the complex relationship between dysfunctional cognitive beliefs, spiritual guilt, and mental repetitions in the development and perpetuation of OCD symptoms, especially in cases where religious themes predominate, a subtype often termed scrupulosity. The paper explores how unconscious feelings of guilt, fear of divine punishment, and rigid or distorted religious beliefs intensify obsessive-compulsive cycles by reinforcing the need for mental or behavioral rituals as a form of atonement or reassurance. It further discusses the limitations of conventional cognitive-behavioral therapy when spiritual dimensions are overlooked and proposes an integrative therapeutic approach that combines evidence-based cognitive restructuring with spiritually sensitive interventions such as emotional release, forgiveness, and reframing of religious narratives. By addressing both psychological and spiritual aspects of the disorder, this holistic approach fosters emotional liberation, reduces symptom severity, and promotes sustained recovery.